Financial hedging of oil in South African organisations - Milambo, Oliver (My University, 2012)
Crude oil is, without doubt, the most important physical commodity as it provides mankind the energy for transportation, industrial and residential use. As a result, it is not surprising that crude oil is the world’s most actively traded commodity. The importance of oil and its extreme price volatility has increased demand for risk management operations and oil industry participants have resorted to the use of derivatives to reduce their exposure. This research seeks to explore the hedging of oil in South African organisations. The study explores the motive for hedging fuel, the type of instruments used to hedge the fuel, the importance of formal hedging policies and the use of software in enforcing controls and ensuring an appropriate level of oversight in the execution and reporting of hedging activities. Data gathering consisted of semi-structured interviews with senior personnel involved in hedging within their organisations. The research objective was broken down into a number of propositions derived from the literature review. The results showed strong support for the proposal that South African organisations hedge to protect the fuel price risk, thereby managing the cash flows. There was also strong evidence that organisations use swaps and over the counter (OTC) traded options. However, there was little support for the use of exchange traded instruments. South African companies consider formal policies and procedures as critical for their hedging activity. The majority of the companies in the study valued the use of software tools for the execution and management of hedges to ensure a fit with the company’s goals and risk management policy. More companies used inhoused developed software as opposed to purchased derivatives software.
MBA thesis - WBS
Keywords: Hedging; Financial hedging; Oil industry